المهمش في شعر عبيد بن أيوب العنبري - الدليمي م.د. جمانة محمد نايف (lark, 2020)
The marginal study in the poetry of Obaid bin Ayoub al-Ansari reflects the status of fear and panic that this poet has lived after his blood, and his escape from the tribe after this, and his displacement was in the desert. Fear was two dimensions Section of searching for an inventor’s first aspect highlighted the spatial marginalization and focused on where and all the details of the beast, unity and unity and what is surrounded by the mirror and male mentioned by the poet Tara by the statement and the telephone and other marginalization. The second study was allocated to marginalization (the other) and what this marginalization involves the affiliation, strength and righteousness.